حدت پاستورلا مولتوسیدا سروتیپ A1 برای جوجه ها و موشها - ا. ستوده نیا; سعید عطایی; غ.ر. موذنی; احمدرضا جباری; م. طباطبایی (Archives of Razi Institute, 2004)
The virulence of Pasteurella multocida (P. multocida) serotype A1 for chickens and mice was determined. Groups of chicken and mice were exposed intramuscularly and intraperitoneally to various concentration of P. multocida broth culture, respectively. This strain was highly virulent for chickens so that those exposed to only 7 c.f.u. of the organism died in less than 24 hours. Groups of mice exposed to the virulent strain died during 48 hours post inoculation. Microbiological examination resulted in the isolation of P. multocida from exposed chicken and mice. No isolation was made from unexposed control groups. The result indicates that the isolate is highly virulent for both chickens and mice.